The Effect of Endorphin Massage on the Intensity of Back Pain in Mothers During Active Phase I in Labor in Tegallega Village, Warungkondang District, Cianjur Regency, Indonesia - Rika Dwi Mustika; Paramita Mustari (HM Publisher, 2023)
Childbirth is a physiological process or the process of expelling viable products of conception from the uterus to the outside world, thus enabling the mother to give birth to her fetus through the birth canal. There are several aspects related to pain during labor and can affect the birth process itself. Treatment uses non-pharmacological methods such as relaxation, warm compresses, yoga and one of which is using massage methods to reduce pain, one of which is back massage and endorphin massage. This study aimed to find out the effect of endorphin massage on the intensity of back pain in laboring mothers during the first active phase in Tegallega Village, Warungkondang District, Cianjur Regency. This study is an experimental research with a one group pre-test post-test design. This research only involves one group of subjects who will be observed before and after the intervention. The average intensity of pain before endorphin massage was given to mothers giving birth was 8.23. Meanwhile, the average value of the intensity of back pain in women giving birth after being given endorphin massage was 7.23. This shows that the intensity of back pain in mothers giving birth during the first active phase before endorphin massage was given to mothers giving birth during the first active phase in Tegallega Village decreased. There is an effect of giving endorphin massage on the intensity of back pain in mothers giving birth during the first active phase.